Global and regional burden of bloodstream infections caused by carbapenem-resistant Gram-negative bacteria in 2019: A systematic analysis from the MICROBE database - Lei Zha; Shirong Li; Jun Guo; Yixin Hu; Lingling Pan; Hanli Wang; Yun Zhou; Qiancheng Xu; Zhiwei Lu; Xiang Kong; Xinzhao Tong; Yusheng Cheng (International Journal of Infectious Diseases)
Objectives: To quantify the global and regional burden of bloodstream infections associated with and attributable to carbapenem-resistant Gram-negative bacteria. Methods: We extracted data from the Measuring Infectious Causes and Resistance Outcomes for Burden Estimation database, which includes the estimated burden of 23 pathogens and 88 pathogen-drug combinations across 12 major infectious syndromes globally in 2019. The number and rate of deaths, as well as disability-adjusted life-years linked to bloodstream infections, were systematically analyzed. Results: In 2019, bloodstream infections accounted for approximately 2.91 (95% UI, 1.74-4.53) million deaths globally, with Gram-negative bacteria responsible for 51.1% of these fatalities. An estimated 391,800 (95% UI 221,500-631,400) deaths were associated with carbapenem resistance, constituting 26.3% of all bloodstream infection-related deaths. The highest burden of carbapenem resistance was seen in South Asia, East Asia, and Eastern Europe, while the lowest burden was in Sub-Saharan Africa. Notably, Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa were the leading carbapenem-resistant pathogens contributing to mortality. Conclusions: Our findings underscore the significant global burden of bloodstream infections caused by carbapenem-resistant Gram-negative bacteria, with notable regional disparities. There is an urgent need for enhanced surveillance, improved infection prevention and control measures, and better access to first-line antibiotics, particularly in high-burden regions.